Information, communication, travel behavior and accessibility - Bert van Wee; Karst Geurs; Caspar Chorus (Journal of Transport and Land Use, 2013)
Over the past two decades many papers have been published on the impact of Information and Communication Technologies (ICT) on travel behavior, but the literature focusing on the impact of ICT on accessibility is relatively scarce. In this paper we give an overview of the impact of ICT on four components of accessibility as distinguished by Geurs and van Wee (2004): (1) the land-use component, (2) the transportation component, (3) the temporal component, and (4) the individual component. Conclusions are that first much more literature exists on the potential impacts of ICT on travel behavior than on its impact on accessibility. Second, we argue that ICT potentially has an impact on all four components of the concept of accessibility. Literature exists on the direct impacts but fails to incorporate impacts due to the interactions between the accessibility components. Third, there seems to be a major challenge in developing accessibility measures and indicators that include ICT, including those that measure the utility of accessibility. Fourth, in the area of ICT’s impact on travel behavior, many research gaps exist. Examples are the impact of ICT on overall activity and trip patterns, the impact of ICT on activities and trips at the household and social-network level, ICT as a means of avoiding congestion or mitigating its effects, and the role of the phenomenon of self-selection in the context of ICT use. Finally, a major challenge is to develop models for activities, including ICT-impacts, which combine high levels of behavioral realism with (econometric) tractability.